Adaptação em novos tempos: análise das ações de marketing dos músicos no mercado da Grande Vitória - Corrêa, Henrique Lucas Sarafim (2023)
This study aimed to analyze the marketing actions of rock bands from Grande Vitória, Espírito Santo, amid the new contexts of the music market. To achieve this goal, specific objectives were defined, including the characterization of the participating bands, the identification of musicians' roles, the description of marketing actions used, and the analysis of communication tools employed by the bands. The theoretical framework encompassed relevant concepts such as the transformation of the music market, strategies applied to the music industry, the relationship between the audience and music, and the application of the marketing mix in music, presented by Hracs (2012), Pascuci and Alves (2018), Kamp (2010), and Hull, Hutchison, and Strasser (2011), respectively. The methodology involved a qualitative and descriptive approach, conducting semi-structured interviews with musicians from independent bands in the region. Seven musicians were interviewed, selected for not having contracts with major record labels. The Iramuteq software supported the content analysis of the interviews, enabling the identification of thematic categories and relevant patterns in the participants' responses. The results of the research with the rock bands from Grande Vitória highlight the relevance of merchandise sales for financial sustainability and brand strengthening, the effective use of Spotify for global reach, the importance of social media for promotion and interaction with fans, the effectiveness of strategic partnerships in attracting diverse audiences and sharing resources, the value placed on musical quality for standing out, and the recognition of the importance of a unique musical identity. The bands' marketing strategies align with current market trends, emphasizing digital platforms and authenticity. The success of the bands depends not only on their musical skills but also on building and maintaining relationships with other musicians, producers, promoters, and fans.